2022
DOI: 10.3389/fnut.2022.827286
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Plant-Based Foods and Nutraceuticals on Toxoplasma gondii Cysts: Nutritional Therapy as a Viable Approach for Managing Chronic Brain Toxoplasmosis

Abstract: Toxoplasma gondii is an obligate intracellular parasite that mainly infects warm-blooded animals including humans. T. gondii can encyst and persist chronically in the brain, leading to a broad spectrum of neurological sequelae. Despite the associated health threats, no clinical drug is currently available to eliminate T. gondii cysts. In a continuous effort to uncover novel therapeutic agents for these cysts, the potential of nutritional products has been explored. Herein, we describe findings from in vitro an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 172 publications
0
6
0
Order By: Relevance
“…When host immunity decreases in the state of T. gondii latent infection, latent infection is activated, causing severe acute toxoplasmosis again. In clinical studies, patients with solid malignant tumors, solid organ transplant (SOT) ( 26 ), human immunodeficiency virus (HIV)/AIDS, diabetes, and those receiving immunosuppressive agents have a high risk of reactivated toxoplasmosis ( 27 , 28 ). Therefore, reactivation of T. gondii infection is more common in patients with these diseases.…”
Section: Discussionmentioning
confidence: 99%
“…When host immunity decreases in the state of T. gondii latent infection, latent infection is activated, causing severe acute toxoplasmosis again. In clinical studies, patients with solid malignant tumors, solid organ transplant (SOT) ( 26 ), human immunodeficiency virus (HIV)/AIDS, diabetes, and those receiving immunosuppressive agents have a high risk of reactivated toxoplasmosis ( 27 , 28 ). Therefore, reactivation of T. gondii infection is more common in patients with these diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Excysted bradyzoites transform into tachyzoites that proliferate causing widespread inflammation and critical morbidity. In fact, brain cyst reactivation with toxoplasmic encephalitis (TE) is not commonly reported in immunocompetent individuals with latent toxoplasmosis [8] . In their review [8] , the researchers observed that brain cysts were commonly reported in the cerebral cortex, basal ganglia, and cerebellum based on studies conducted on autopsies of AIDS patients with TE [18] .…”
Section: Discussionmentioning
confidence: 99%
“…In fact, brain cyst reactivation with toxoplasmic encephalitis (TE) is not commonly reported in immunocompetent individuals with latent toxoplasmosis [8] . In their review [8] , the researchers observed that brain cysts were commonly reported in the cerebral cortex, basal ganglia, and cerebellum based on studies conducted on autopsies of AIDS patients with TE [18] . Moreover, the reviewers noticed that latent toxoplasmosis negatively affects neurocognitive functions associated with behavioral changes, e.g.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The current first-line therapy for toxoplasmosis includes dihydrofolate reductase inhibitors (pyrimethamine or trimethoprime) and dihydropteroate synthetase inhibitors (sulfadiazine, sulfadoxine or sulfamethoxazole) [ 9 ]. Moreover, clindamycin and atovaquone have been adopted as second-line therapy [ 10 ]. Unfortunately, these clinical drugs are only effective in eliminating tachyzoites in the acute stage and are unable to kill cysts in the chronic stage [ 11 ].…”
Section: Introductionmentioning
confidence: 99%